Pengembangan Multimedia Berbasis Powtoon Materi Bangun Ruang Kelas V SD Negeri Condongcatur - Fatika Chandra Annisa; Tiara Friaesa Harsono; Denisa Ramadhani; Irfan Wahyu Prananto (WASIS : Jurnal Ilmiah Pendidikan, 2022)
This study aims to develop multimedia based on Powtoon in geometry for the fifth grade of SD Negeri Condongcatur. This research was also conducted to determine the appropriateness of the appropriate learning media for elementary school students, especially on geometry. This type of research is Research and Development with a 4-D development model, namely Define, Design, Development, and Disseminate. However, this research is limited to the Development stage only. The subjects of this research are fifth grade students of SD Negeri Condongcatur. The data collection techniques used were observation and interviews for initial needs analysis and questionnaires for the validation process. The data that has been obtained is then analyzed using descriptive qualitative and quantitative descriptive analysis techniques. This study involved one material expert who was a lecturer in Elementary Mathematics Education and one media expert who was a lecturer in Educational Technology as a validator. The results of the validation of material experts on this learning media obtained an average of 96% with a very feasible category. While validation from media experts, this learning media obtained an average result of 92,5% with a very feasible category. The overall validation results obtained by this learning media quantitatively amounted to 94,25% and qualitatively with a very feasible category.